Investigation of nutritional status, VO2max, agility, speed, and strength: A cross-sectional study in basketball athletes - Hudain, Muh Adnan; Kamaruddin, Ilham; Hita, I Putu Agus Dharma; Pranata, Doni; Ariestika, Elsa (Journal Sport Area, 2023)
Nutritional status, VO2max, agility, speed, and strength are very important factors for every athlete to achieve maximum performance, especially in basketball. This study aims to determine the level of nutritional status, VO2max, agility, speed, and strength of Jembrana Regency basketball athletes in Preparation for the 2022 Bali Provincial Sports Week Championship. The sample in this study consisted of 12 men’s basketball athletes, Porprov Jembrana Regency, using the total sampling technique. The type of research used in this research was a cross-sectional study. The instruments used to collect data in this study were the Body Mass Index to measure nutritional status, the Multistage Fitness Test to measure VO2max, the Illinois Agility Test to measure agility, the 30M Sprint Test to measure speed, and the Push Up & Sit Up Test to measure muscle strength; belly and arms. The study found that the average nutritional status was normal, VO2max was good, agility was good, speed was very poor, arm muscle strength was good, and abdominal muscle strength was very good. The results of the study could assist Jembrana Regency get a good idea of how the athletes are training and how well the staff and teachers are working together. This is important for getting the best results at the Bali Provincial Sports Week championship. Based on the study's results, the best way to get ready for the Bali Provincial Sports Week championship is for players to get in better shape, especially in terms of biomotor VO2max and speed, which are still not good enough. So, more study can be done to re-evaluate these biomotors and add more physical test markers so that players’ physical success can be tracked as well as possible.